(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
The death occurring within 24 hour from the onset of symptom was considered as sudden death. About 45-50% sudden deaths are due to cardiovascular diseases. Pancarditis also called perimyoendocarditis, is an inflammation of the entire heart. We have presented a case of 28 years old female was brought to Govt. medical college and hospital Miraj with history of chest pain at home and past history revealed intermittent fever since few days, she was declared dead on arrival in emergency dept.